Clinical Characteristics and Risk Factors of Lung Injury Induced by Nab-Paclitaxel - Yoshioka K; Abe M; Shiko Y; Koshikawa K; Kawasaki Y; Iwasawa S; Terada J; Tsushima K; Tatsumi K; Suzuki T (Dove Medical Press, 2022)
Keiichiro Yoshioka,1 Mitsuhiro Abe,1 Yuki Shiko,2 Ken Koshikawa,1 Yohei Kawasaki,2 Shunichiro Iwasawa,1 Jiro Terada,1,3 Kenji Tsushima,3 Koichiro Tatsumi,1 Takuji Suzuki1 1Department of Respirology, Graduate School of Medicine, Chiba University, Chiba, Japan; 2Biostatistics Section, Clinical Research Center, Chiba University Hospital, Chiba, Japan; 3Department of Pulmonary Medicine, International University of Health and Welfare, School of Medicine, Chiba, JapanCorrespondence: Mitsuhiro Abe, Department of Respirology, Graduate School of Medicine, Chiba University, 1-8-1 Inohana Chuo-ku, Chiba, 260-8670, Japan, Tel +81 43 222 2576, Fax +81 43 226 2176, Email mthrsgnm@chiba-u.jpBackground/Aim: Nab-paclitaxel (Nab-PTX) has been widely used to treat several advanced cancers. Nab-PTX can cause drug-induced lung injury (DILI); however, its clinical and radiographic features have not been clarified. We aimed to assess the clinical characteristics of Nab-PTX-induced lung injury and identify its associated risk factors.Patients and Methods: We retrospectively investigated 304 patients who received Nab-PTX at Chiba University Hospital between November 2010 and November 2017. We obtained information regarding the clinical course, laboratory findings, and chest computed tomography findings from their medical records.Results: Forty-one patients (13%) developed DILI. Grade 1 lung injury occurred in 27 patients (8.8%), grade 2, 8 patients (2.6%); grade 3, 3 patients (0.9%); grade 4, 1 (0.3%); and grade 5, 2 (0.6%). Multivariate analysis revealed that age > 56 years (odds ratio [OR]: 3.0), pre-existing interstitial lung changes (OR: 3.2), and combined drugs with gemcitabine (OR: 2.7) were independent risk factors for DILI owing to Nab-PTX administration.Conclusion: Nab-PTX-induced lung injury is not rare; however, most cases are asymptomatic (grade 1). Older age, pre-existing interstitial lung changes, and combined drugs with gemcitabine could increase the incidence of Nab-PTX-induced lung injury; such patients should be treated with greater care.Keywords: drug-induced lung injury, gemcitabine, multivariate analysis, nab-paclitaxel, risk factor